CRISPR/Cas9-mediated gene editing of vacuolar ATPase subunit d mediates phytohormone biosynthesis and virus resistance in rice - Lu, Qinghua; Luo, Xiangwen; Yang, Xiao; Zhou, Tong; Zhang, Yu; Lan, Ying; Zhang, Deyong; Zheng, Limin; Li, Yixin; Li, Li; Zhang, Songbai; Liu, Yong (Frontiers in Plant Science, 2023)
Vacuolar ATPases (V-ATPases) are proton pumps for proton translocation across membranes that utilize energy derived from ATP hydrolysis; OsV-ATPase subunit d (OsV-ATPase d) is part of an integral, membrane-embedded V0 complex in the V-ATPase complex. Whether OsV-ATPase d is involved in phytohormone biosynthesis and resistance in rice remains unknown. The knockout mutants of OsV-ATPase d in rice were generated using the CRISPR/Cas9 system, and mutation of OsV-ATPase d did not show any detrimental effect on plant growth or yield productivity. Transcriptomic results showed that OsV-ATPase d is probably involved in mediating the biosynthesis of plant hormones and resistance in rice. Compared to wild type, mutation of OsV-ATPase d significantly increased JA and ABA biosynthesis and resistance against Southern rice black-streaked dwarf virus (SRBSDV), but it decreased resistance against Rice stripe virus (RSV) in rice. The data presented in this study reveal that OsV-ATPase d mediates phytohormone biosynthesis and virus resistance in rice and can be selected as a potential target for resistance breeding in rice.